29 November 1795 Kahramanmaraş Earthquake, Southern Turkey - Paluto?lu, Mahmut; Şaşmaz, Ahmet (General Directorate of Mineral Research and Exploration (MTA), 2017)
Major tectonics on the Kahramanmaraş region are the northern strand of EAFZ (Sürgü fault zone, Çardak segment, Savrun segment and Toprakkale segment) and the southern strand of EAFZ (Gölbaşi segment, Amanos sgment), Engizek Fault Zone, Kahramanmaraş Fault Zone and The Narli segment of DSFZ. An earthquake, occurred in Kahramanmaraş, 1795, is mentioned a manuscript named Divan-i Hasmi which is found at Koyuno?lu Library in Konya. According to manuscript the Mercalli Intensity of the earthquake has calculated as eight and the magnitude is seven. The calculations made have strengthened the possibility of earthquake occurncy on the Gölbaşi segment of EAFZ.
Keywords: East Anatolian Fault Zone; Historical Earthquake; Intensitiy; Kahramanmaraş; Manuscript